New Trends in Green Projects Aimed at Clean Energy: An Analysis of the Scientific Literature - Hernandez-Palma, Hugo Gaspar; Novoa, Dairo J.; Álvarez, Jorge Enrique Taboada (International Journal of Energy Economics and Policy, 2024)
In the search for global sustainability of energy production, green projects focused on clean energy have become a top priority internationally. Therefore, in order to understand current trends in this field, this bibliometric study has been developed. Through the analysis of scientific publications, key lines of research have been identified in the field of sustainable energy. The study used data from Scopus to analyze the trends of green projects focused on clean energy in the period between 2002 and 2024. The results obtained reveal a growth rate of 7.59% in scientific production in recent years, finding a total of 122 documents from 96 different sources and contributions from 344 authors. China is the country that leads in scientific productivity during the mentioned period, followed by India and the United States. The most prolific journals include Journal of Cleaner Production and Resources Policy, institutions such as IBN Tofail University and WSB University have been revealed as prominent contributors, and Taghizadeh-Hesary F is listed as the main author found in the analysis. Finally, keywords such as “sustainable development,” “renewable energy,” “green projects,” “renewable energy resources,” “global warming,” and “land fill” dominate the discourse, reflecting a global emphasis on sustainable energy solutions. The findings of this research serve as a guide for researchers, policymakers, green technology investors and project managers to formulate future solutions aimed at an effective energy transition on a global scale.